Amazing frogs & toads - Clarke, Barry; Young, Jerry (New York : Knopf : Distributed by Random House, 1990)
Text and photographs introduce members of the frog and toad world and describe their unique characteristics.
Includes index.
Children's Catalog (Wilson)
5.3
K-3
Keywords: Frogs -- Juvenile literature; Toads -- Juvenile literature; Frogs; Toads; Frogs; Toads